The “outsourcing” as an instrument of competitiveness in the business consulting industry - Lopes da Costa, R.; António, N. (Journal of Management Research, 2011)
In an era of particularly intense competition, the consulting services are becoming an increasingly important source of aid for strategic making and an important way to increase efficiency and quality in the various business activities, being seen by many managers as an influential and powerful tool for organizational change, bringing new life to the organization and procedural chain of the company. The purpose of this article is to emphasize exactly this situation, showing from a case study carried out in one of the biggest Portuguese private banks the real value of professional advice when you combine a broad view of business to study a set of skills closely linked to the relationship between service / market, focusing on "core" competencies, resources and offers increasingly facilitating the well being of the client, fostering creativity and dynamism in the activities of companies operating through the potentials of TIG (information technology management).